PENGUKURAN COMPUTED TOMOGRAPHY DOSE INDEX (CTDI) PADA FANTOM KEPALA DENGAN MENGGUNAKAN CT DOSE PROFILER - Ahadiyah, Naeli Ni'matin; Setiawati, Evi; Arifin, Zaenal; Anam, Choirul (BERKALA FISIKA, 2020)
This study aims to  measure  computed  tomography  dose  index (CTDI) on  a  head  polymethyl methacrylate (PMMA) phantom using a CT dose profiler for various slice thicknesses. The slice thicknesses were 3, 5, and 10 mm. Dose measurements were performed in spiral mode for every hole  within  the  head  PMMA  phantom.  A  CT  dose  profile  analyzer  software  integrated  the profile  dose  along  100  cm  to  find  the  CTDI100.  The  CTDIw  was  calculated  as 1/3×(CTDI100,center)+2/3×(average CTDI100, perifer). Since the pitch was unity, the CTDIvol was similar to the CTDIw. The values of CTDIvol for slice thickness variations were from 45.7 mGy to 46.0 mGy.  This result indicated that there is no significant different of CTDIvol measured using CT dose profiler for slice thicknesses from 3 mm up to 10 mm.Keywords: CT dose profiler, CTDI, CTDI100, CTDIw, CTDIvol, slice thickness